Developing a technology-mediated reading comprehension tasks to scaffold learners in the building of negotation skills - Kassim, Asiah; Kassim, Hafizoah; Nur Syafawati, Sabuan (2018)
This study reports the development of an online platform to classify and store students’ reading comprehension achievements data that are aligned with the Common European Framework of Reference (CEFR) in order to ensure that the learning process can meet the international standard while conscientiously tailored to the specific learners’ needs. The theoretical foundation of the study is the integration between instructional design (ID) and CALL frameworks. Kemp’s ID Model (cited in Morrison et al., 2010) is the basis for the software development supported by the Chun’s (2016) recent framework on Ecological CALL that is in line with CEFR practices. The basis for classification of the achievements includes selection of reading texts and development of the questions that are vetted aligning to the CEFR levels. The online platform comprises a database which integrates the information on the CEFR reading illustrative tasks and the scoring grids that would automatically sort the scores of reading comprehension tasks to the CEFR levels accordingly. The system may be able to contribute to the language teaching and learning, with a specific focus on the development of reading skills. Additionally, with the recent emphasis on CEFR, the system may be able to assist teachers to provide appropriate reading comprehension tasks to meet students’ level, and for students to map their language competency to the CEFR levels.